2009
DOI: 10.1111/j.1467-8624.2009.01337.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Background Television on Parent–Child Interaction

Abstract: This study investigated the hypothesis that background television affects interactions between parents and very young children. Fifty‐one 12‐, 24‐, and 36‐month‐old children, each accompanied by 1 parent, were observed for 1 hr of free play in a laboratory space resembling a family room. For half of the hour, an adult‐directed television program played in the background on a monaural television set. During the other half hour, the television was not on. Both the quantity and quality of parent–child interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
215
5
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(264 citation statements)
references
References 31 publications
5
215
5
13
Order By: Relevance
“…7 The instant accessibility and portability of mobile devices make them potentially more likely to displace human interactions and other enriching activities. Because thousands of apps are marketed as "educational" (without evidence for this claim), parents may feel comfortable with this relative increase in screen time.…”
Section: Displacement Of Activitiesmentioning
confidence: 99%
“…7 The instant accessibility and portability of mobile devices make them potentially more likely to displace human interactions and other enriching activities. Because thousands of apps are marketed as "educational" (without evidence for this claim), parents may feel comfortable with this relative increase in screen time.…”
Section: Displacement Of Activitiesmentioning
confidence: 99%
“…9 These effects may be more pronounced in lowincome populations, where high media exposure is more prevalent. 2 Proposed mechanisms for these detrimental effects include replacement of enriching activities with caregivers, 10 reduced language-based and play interactions with parents, [11][12][13] and less creative child play 14 while the TV is on.…”
mentioning
confidence: 99%
“…TV can impact not only quantity of time spent but also the quality. In the presence of a TV parents have been shown to be less attentive, engaged, spend less time speaking to their children and speak to them in shorter sentences (Christakis, 2009;Kirkorian, Pempek, Murphy, Schmidt, & Anderson, 2009;Mendelsohn et al, 2008;Tanimura, Okuma, & Kyoshima, 2007). In fact when Zimmerman et al (2009) statistically controlled for child-directed parental language, the negative effect of TV viewing on language development was entirely eliminated.…”
Section: Mechanisms By Which Screen Time Might Impact Developmentmentioning
confidence: 86%
“…Research has found that rapid visual and auditory changes can distract young children from exploration and toy playtime as their attention is directed towards the screen numerous times during a play session (Schmidt, Pempek, Kirkorian, Lund, & Anderson, 2008). Background TV also reduces the quality of parent-child interaction as parents too can get distracted by what is on the screen and therefore can spend less time engaging with the child (Kirkorian, Pempek, Murphy, Schmidt, & Anderson, 2009). Cognitive processing, memory and reading comprehension can also be negatively affected by the presence of background TV (Armstrong & Greenberg, 1990;Barr, Lauricella, Zack, & Calvert, 2010;Schmidt et al, 2008;Vandewater et al, 2005).…”
Section: The Impact Of Background Tv On Child Outcomesmentioning
confidence: 99%